2007
DOI: 10.1124/mol.106.031427
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Adenosine A1Receptor Inhibits HIV-1 Tat-Induced Apoptosis by Reducing Nuclear Factor-κB Activation and Inducible Nitric-Oxide Synthase

Abstract: Human immunodeficiency virus dementia (HIV-D) is a nonfocalcentral nervous system manifestation characterized by cognitive, behavioral, and motor abnormalities. The pathophysiology of neuronal damage in HIV-D includes a direct toxic effect of viral proteins on neuronal cells and an indirect effect caused by the release of inflammatory mediators and neurotoxins by activated macrophages/microglia and astrocytes, culminating into neuronal apoptosis. Previous studies have documented that the nucleoside adenosine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…Previous studies have indicated that round window application of R-PIA reduced cisplatin-induced hearing loss and hair cell damage (Whitworth et al, 2004). In this study, we showed a similar effect of R-PIA when administered by the trans-tympanic route.…”
Section: Activation Of a 1 Ar Prevented Cisplatin-induced Hearing Lossupporting
confidence: 73%
See 4 more Smart Citations
“…Previous studies have indicated that round window application of R-PIA reduced cisplatin-induced hearing loss and hair cell damage (Whitworth et al, 2004). In this study, we showed a similar effect of R-PIA when administered by the trans-tympanic route.…”
Section: Activation Of a 1 Ar Prevented Cisplatin-induced Hearing Lossupporting
confidence: 73%
“…Additional studies have also shown that the chemotherapeutic agent cisplatin induces the expression of the cochlear A 1 AR, which likely represents a compensatory mechanism by the cochlea to counter the toxic effects of increased ROS generation by cisplatin (Ford et al, 1997b). Activation of A 1 AR was also shown to confer protection of OHCs against cisplatin-induced damage and death and hearing loss (Whitworth et al, 2004;Gunewardene et al, 2013). However, it has been suggested that A 1 ARs are not localized to OHCs, but rather are found on IHCs, Deiter's cells, and spiral ganglion (SG) neurons (Vlajkovic et al, 2009).…”
Section: A 1 Ars Are Expressed On Cochlear Ohcsmentioning
confidence: 99%
See 3 more Smart Citations